Planning for Human-Wildlife Coexistence: Conceptual Framework, Workshop Process, and a Model for Transdisciplinary Collaboration - Marchini, Silvio; Ferraz, Katia M. P. M. B.; Foster, Vania; Reginato, Thiago; Kotz, Aline; Barros, Yara; Zimmermann, Alexandra; Macdonald, David W. (Frontiers in Conservation Science, 2021)
Coexistence, as a concept and as a management goal and practice, has attracted increasing attention from researchers, managers and decision-makers dedicated to understanding and improving human-wildlife interactions. Although it still lacks a universally agreed definition, coexistence has increasingly been associated with a broad spectrum of human-wildlife interactions, including positive interactions, transcending a conservation focus on endangered wildlife, and involving explicitly considerations of power, equity and justice. In a growingly complex and interconnected human-dominated world, the key to turning human-wildlife interactions into large-scale coexistence is thorough planning. We present an approach for evidence-based, structured, and participatory decision-making in planning for human-wildlife coexistence. More specifically, we propose (i) a conceptual framework for describing the situation and setting the goals, (ii) a process for examining the causes of the situation and creating a theory of change, and (iii) a model for transdisciplinary research and collaboration integrating researchers, decision-makers and residents along with the interests of wildlife. To illustrate the approach, we report on the workshop considering the Jaguars of Iguaçu, a conservation project whose strategy includes the improvement of the relationship between ranchers and jaguars outside Iguaçu National Park, Brazil.